2014
DOI: 10.1007/s00208-013-1004-4
|View full text |Cite
|
Sign up to set email alerts
|

Generic non-selfadjoint Zakharov–Shabat operators

Abstract: In this paper we develop tools to study families of non-selfadjoint operators L(ϕ), ϕ ∈ P , characterized by the property that the spectrum of L(ϕ) is (partially) simple. As a case study we consider the Zakharov-Shabat operators L(ϕ) appearing in the Lax pair of the focusing NLS on the circle. The main result says that the set of potentials ϕ of Sobolev class H N , N ≥ 0, so that all small eigenvalues of L(ϕ) are simple, is path connected and dense.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Next we argue as in the proof of Corollary 3.3 in [14] to construct a continuous path : γ : [0, 1] → U tn ∩ iL 2 r so that γ(0) = ψ (0) , γ(1) = ψ (1) , and for any potential ϕ ∈ γ [0, 1] the operator L(ϕ) has only simple (and hence non-real) periodic eigenvalues in the disk B R ′ . In view of the compactness of γ we can find a connected open neighborhood…”
Section: Angles On the Neighborhood U Tnmentioning
confidence: 93%
See 2 more Smart Citations
“…Next we argue as in the proof of Corollary 3.3 in [14] to construct a continuous path : γ : [0, 1] → U tn ∩ iL 2 r so that γ(0) = ψ (0) , γ(1) = ψ (1) , and for any potential ϕ ∈ γ [0, 1] the operator L(ϕ) has only simple (and hence non-real) periodic eigenvalues in the disk B R ′ . In view of the compactness of γ we can find a connected open neighborhood…”
Section: Angles On the Neighborhood U Tnmentioning
confidence: 93%
“…This part of the phase space contains the set of potentials ϕ ∈ iH N r which have the property that all multiple eigenvalues are real with geometric multiplicity two whereas all simple eigenvalues are non-real and appear in complex conjugated pairs. In [14], it is shown that this set is open and path connected. We remark that in order to prove that the actions and the angles, first defined in an open neighborhood of the potential ψ ∈ iH N r , analytically extend to an open neighborhood of Iso o (ψ), we make use of the assumption that all periodic eigenvalues of L(ψ) are simple.…”
Section: Methods Of Proofmentioning
confidence: 99%
See 1 more Smart Citation
“…• . Then L 2 • is open, dense, and contains the zero potential ( [10]). In the case of the defocusing NLS equation, L(ϕ) is self-adjoint.…”
Section: Introductionmentioning
confidence: 99%
“…">IntroductionDirac operators attracted considerable attention in recent years, in particular in the context of non-self-adjoint spectral theory [4,5,6,9,12,24,25], nonlinear Schrödinger equations e.g. [3,21] or as an effective model for graphene [1,7,15,20]. In this paper we analyze eigenvalues emerging from the thresholds of the essential spectrum of the one-dimensional Dirac operator in L 2 (R) perturbed by a general matrix-valued and non-symmetric potential V preserving the essential spectrum.Our main results include the existence and asymptotics of weakly coupled eigenvalues for the one dimensional Dirac operator (Theorem 2.2) and Lieb-Thirring type inequalities (Theorem 2.4) in the massive as well as the massless case.…”
mentioning
confidence: 99%